Changes in the functional traits of Thymus mongolicus along environmental gradients and factors influencing the traits of Northern China - Mi, Wentao; Zheng, Hao; Zhang, Haixuan; Zhang, Wanyu; Chi, Yuan; Ren, Weibo (Frontiers in Plant Science, 2025)
Thymus mongolicus is a common medicinal and edible plant in grasslands of northern China. However, previous studies were limited to the production and utilization value of T. mongolicus, and only few studies have paid attention to the changes in the functional traits of wild T. mongolicus on a large scale. Therefore, this study examined 145 T. mongolicus specimens collected from northern China. By measuring 10 functional traits, including leaf length, leaf width, and leaf area, we analyzed the interplay between functional traits as a response to changes in environmental factors. Significant differences were observed between the eastern and western populations of T. mongolicus. Functional traits exhibited pronounced latitudinal and longitudinal gradients. With increasing latitude and longitude, T. mongolicus tended to change its functional traits to adapt to environmental changes. In high-temperature and high-rainfall environments, T. mongolicus developed larger leaf areas and longer leaves. Random forest analysis identified temperature within the latitudinal and longitudinal context as the primary driver of functional trait variation. Furthermore, interdependencies among functional traits were evident, with specific traits—such as stem length, leaf width, and leaf area—emerging as central to the adaptive process. These findings elucidate the mechanisms and key factors underlying the functional trait adaptation of T. mongolicus, providing critical insights for the breeding of region-specific varieties in China.